Learning English as a Second Language: Orientations Among the Undergraduate Students of Business Administration in Southern Punjab - UZMA SADIQ; NAZIA SULEMAN; MUHAMMAD ZAHID NAWAZ; IRAM GUL (Journal of Business & Tourism, 2021)
The motivation to learn English as a second language is always motivated through different orientations which are of ultimate interest to the researchers. These orientations are originating from both integrative as well as instrumental conceptualizations. As the lingua franca is English so these orientations are becoming more complex. In Pakistan, where English is used as L2 new orientations are emerging with the growing needs. The factor analysis employed by Mansoor (2015) in Khyber-Pakhtunkhwa is taken as a model framework to study the same in Southern Punjab (Pakistan). For the current study a sample of 150 students of Business Administration Department of universities at Southern Punjab were taken as a population for the factor analysis. The findings support the fact that the integrative factor which is „Matter of Dignity‟ towards studying English as a second language from the available set of orientations is a stronger factor among the undergraduate students of Southern Punjab.